Multidrug resistance bacteremia in neonates and its association with late-onset sepsis and Coagulase-negative Staphylococci - Quispe, Antonio M. (2020)
Introduction: This study aimed to assess the association between multidrug resistance (MDR) and late-onset sepsis (LOS) among newborns with bloodstream infection (BSI). Methodology: In this cross-sectional study, we routinely tested every newborn with a presumptive diagnosis of sepsis admitted to the largest reference maternity hospital in Lima, Peru for BSI over an 18-month period. We tested every isolate for MDR by using the disk-diffusion method and assessed its associated factors by using a robust Poisson regression analysis with a particular focus on its association with LOS (vs. early-onset sepsis, EOS). Results: We analyzed a total of 489 subjects, including 340 (69%) newborns with LOS, and estimated an MDR rate of 80% (95% confidence interval, CI: 76%-83%), which was significantly higher (p-value < 0.001) among LOS (85%; 95% CI: 81%-89%) than EOS cases (67%; 95% CI: 59%-75%). The primary isolate was coagulase-negative Staphylococci (CoNS) (60%), which exhibited a limited subset of antibiotic MDR patterns, most of which were characterized by their resistance to cefoxitin, gentamicin, and clindamycin and levofloxacin. Overall, the prevalence of MDR was higher among LOS compared to EOS cases (adjusted prevalence ratio [aPR] = 1.28; 95% CI: 1.14-1.45), and among BSI due to CoNS compared to other bacteria (Apr = 1.10; 95% CI: 1.01-1.20).